Efficacy and Safety of Cryotherapy in "See and Treat" Program in Jakarta Primary Health Centre - Lestari, Linda; Purwoto, Gatot; Nuranna, Laila (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To evaluate the efficacy and safety of cryotherapy in "See and Treat" program in Jakarta Primary Health Care. Method: Using descriptive cross-sectional design, data from medical records were taken with total sampling method. We took the VIA result, cryotherapy procedure, first-marriage age, number of marriage, parity, smoking habit, and the use of contraception. Data were analyzed univariately. Result: Of 86 data, the percentage of cryotherapy to change from positive to negative of VIA result was 90.70%. We did not find the progressivity to invasive cancer. Conclusion: Cryotherapy is effective to manage the cervical precancerous lesion in "See and Treat" program. [Indones J Obstet Gynecol 2016; 4-4: 227-233] Keywords: cryotherapy, Indonesia, see and treat, visual inspection of acetic acid (VIA)